Analisis Break Even Point (BEP) dalam Manajemen Perkebunan Kelapa Sawit: Kajian Konseptual dan Implikasinya terhadap Produktivitas Sumber Daya Manusia: Break Even Point (BEP) Analysis in Oil Palm Plantation Management: A Conceptual Study and Its Implications for Human Resource Productivity - Eli Nasution (Jurnal Kolaboratif Sains, 2026)
Oil palm plantation is a strategic sector in the Indonesian economy, yet its sustainability heavily depends on effective cost management. This article aims to examine the concept of Break Even Point (BEP) as a cost-volume-profit analysis tool in oil palm plantation management, covering its definition, underlying assumptions, calculation methods, factors causing its shift, and its impact on production costs and human resource (HR) productivity. The study was conducted descriptively and qualitatively through a literature review and an illustrative calculation for a 500-hectare division, complemented by sensitivity analysis and corporate case studies. The results show that the example division's BEP is reached at a production level of 4,167 tons of fresh fruit bunches (FFB) per year, well below normal capacity, providing an adequate margin of safety. A decline in FFB price proved to be the most sensitive factor, where a 20% price drop could raise the BEP by 57.8%. An upward shift in BEP directly affects workload, wage systems, training, and the welfare of plantation workers. Recommended management solutions include cost efficiency through precision agriculture, income diversification, HR productivity improvement, CPO price hedging, fixed-cost consolidation through shared services, and KPI-based performance management. This study provides a practical framework for plantation management to continuously monitor and control its BEP position.